A New Conulariid (Cnidaria, Scyphozoa) From the Terminal Ediacaran of Brazil - Leme, Juliana M. (2022)
Paraconularia ediacara n. sp., the oldest documented conulariid cnidarian, is described based on a compressed thin specimen from the terminal Ediacaran Tamengo Formation near Corumbá, Mato Grosso do Sul State, Brazil. The conulariid was collected from a laminated silty shale bed also containing Corumbella werneri and vendotaenid algae. The specimen consists of four partial faces, two of which are mostly covered, and one exposed corner sulcus. The two exposed faces exhibit 32 bell-curve-shaped, nodose transverse ribs, with some nodes preserving a short, adaperturally directed interspace ridge (spine). The transverse ribs bend adapertureward on the shoulders of the corner sulcus, within which the ribs terminate, with the end portions of the ribs from one face alternating with and slightly overlapping those from the adjoining face. This is the first Ediacaran body fossil showing compelling evidence of homology with a particular conulariid genus. However, unlike the periderm of Phanerozoic conulariids, the periderm of P. ediacara lacks calcium phosphate, a difference which may be original or an artifact of diagenesis or weathering. The discovery of P. ediacara in the Tamengo Formation corroborates the hypothesis, based in part on molecular clock studies, that cnidarians originated during mid-late Proterozoic times, and serves as a new internal calibration point, dating the split between scyphozoan and cubozoan cnidarians at no later than 542 Ma. Furthermore, P. ediacara reinforces the argument that the final phase of Ediacaran biotic evolution featured the advent of large-bodied eumetazoans, including, possibly, predators.